Peranan Sistem Informasi Manajemen Bagi Kepala Sekolah Dalam Pengambilan Keputusan di Madrasah Tsanawiyah Pondok Pesantren Amanah Tarbiyah Islamiyah Rempak Kabupaten Siak - Murniati, Sarly; Irawati; Setyaningsih, Rini; Sabrifha, Eli (EL-EMIR Institute, 2024)
This study is entitled the role of management information systems for principals in decision making at Madrasah Tsanawiyah, Islamic boarding school Amanah Tarbiyah Islamiyah Rempak, Siak Regency. The objectives of this study: 1. To determine the characteristics of the education management system at MTs PP-Amti Rempak. 2. To determine the role of management information systems in supporting the principal's decision making at MTs PP-AMTI Rempak. 3. To determine the supporting and inhibiting factors of the management information system in supporting the principal's decision making. The method used in (Syamsudin n.d.) this study is qualitative with descriptive analysis. The main informant of this study is the principal, while the supporting informants are the administrative staff, the vice principal of curriculum, the vice principal of facilities and infrastructure and the coordinator of teaching and education personnel. With data collection, namely observation, interviews, and documentation. After the researcher analyzed with data collection, data reduction, data presentation and drawing conclusions. The results of the study stated that 1) the characteristics of the management information system have been applied. Starting from its human resources where this component is tasked with processing data in the position determined by the principal. Furthermore, for the hardware, it is supported by tools used to store and archive documents. Then for the software, it uses the EMIS application to process data. Then for the information system data resources, it can be arranged, stored, and accessed. And finally, for the communication network, it is equipped with a modem to access the internet. 2) In decision-making activities, the role of the educational management information system has helped the head of the madrasah, to obtain data and information related to facilities and infrastructure, curriculum and teaching and education personnel that can be used to help solve existing problems. 3) The supporting factors for the management information system in the principal's decision-making are human resources (HR) teachers and administrative staff who have met the teacher standards, namely bachelor's degrees. While the inhibiting factor is the lack of administrative staff in managing the management information system.